Poverty and child behavioral problems: the mediating role of parenting and parental well-being - Till Kaiser; Jianghong Li; Matthias Pollmann-Schult; Anne Y. Song (International journal of environmental research and public health, 2017)
The detrimental impact of poverty on child behavioral problems is well-established, but the mechanisms that explain this relationship are less well-known. Using data from the Families in Germany Study on parents and their children at ages 9–10 (middle childhood), this study extends previous research by examining whether or not and to what extent different parenting styles and parents' subjective well-being explain the relationship between poverty and child behavior problems. The results show that certain parenting styles, such as psychological control, as well as mothers' life satisfaction partially mediate the correlation between poverty and child behavioral problems.
Keywords: 330; poverty; life satisfaction; parenting; child behavior problems; Germany